Sosialisasi dan Pelatihan Penyediaan Akomodasi Home Stay di Desa Belumbang Kecamatan Kerambitan Kabupaten Tabanan - I Made Gede Darma Susila; Ni Luh Putu Sri Widhiastuty; I Putu Agus Nurjaya (Pubfine Media Group, 2024)
This study aims to evaluate the socialization and training activities on homestay accommodations in Belumbang Village, Kerambitan Sub-district, Tabanan Regency. The research uses a qualitative descriptive approach with data collection techniques including participatory observation and structured interviews with participants and program organizers. The findings indicate that the socialization and training activities successfully enhanced the community's understanding of the concept and practice of homestay accommodation. Active participation from the community in these activities also strengthened the relationship between local government and the local community. However, challenges remain in the program's implementation, such as the need for further support in homestay management and marketing. This study concludes that socialization and training activities are a positive first step in developing the tourism potential of Belumbang Village, but continuous efforts are needed to ensure the sustainability and success of the homestay program in the future.